Epidemiology and immunodiagnostics of Strongyloides stercoralis infections among migrant workers in Malaysia - Sahimin, Norhidayu; Lim, Yvonne Ai Lian; Noordin, Rahmah; Yunus, Muhammad Hafiznur; Arifin, Norsyahida; Behnke, Jerzy Marian; Mohd Zain, Siti Nursheena (Medknow Publications, 2019)
To investigate the status of Strongyloides(S.) stercoralis infections among migrant workers in Malaysia for the first time and identify risk factors. Methods: Four diagnostic methods were employed for the detection of S. stercoralis including microscopy, enzyme-linked immunosorbent assay (ELISA) using a commercial kit, ELISA using the rSs1a antigen and polymerase chain reaction (PCR). Low and semi-skilled workers from five working sectors (i.e. manufacturing, food service, agriculture and plantation, construction and domestic service) were tested on a voluntary basis. Results: The overall seroprevalence of S. stercoralis from 483 workers employing the ELISA commercial kit for IgG was 35.8% (n=173; 95% CI: 31.5%-40.1%) whereas seroprevalence using the rSs1a-ELISA was 13.0% (n=63; 95% CI: 10.0%-16.0%). Cross tabulation between the ELISA commercial kit and rSs1a-ELISA showed that only 6.4% (n=31; 95% CI: 4.2%-8.6%) of the samples were positive in both tests. Microscopic examination of all 388 fecal samples were negative; however subsequent testing by a nested PCR against DNA from the same samples successfully amplified DNA from three male subjects (0.8%; 3/388). Male workers, India and Myanmar nationality, food service occupation and those living in the hostel were statistically significant with seroprevalence (P<0.005). Conclusion: This is the first report on the epidemiology of S. stercoralis infections among the migrant workers in Malaysia. Our results highlight the importance of using appropriate diagnostic tools for detection. The presence of anti-S. stercoralis antibodies in the study population calls for improvements in personal hygiene and sanitation standards among migrant workers in Malaysia through control strategies including health education campaigns and programs aimed at increasing awareness and healthy behaviors. © 2019 Asian Pacific Journal of Tropical Medicine Produced by Wolters Kluwer-Medknow. All rights reserved.